La citación de la demanda en los juicios por deudas, a través de una radioemisora y el derecho a la intimidad. - Pinos Chafla, Sherevin Johanna (2023)
: The present research determines the incidence of the summons to the defendant through a radio station and analyzes if the exercise of this procedural act contemplated in article 56 numeral 2 of the General Organic Code of Processes violates the right to privacy. The methodology used is descriptive, non-experimental research with a historical- logical method and non-experimental design, focusing its analysis specifically on the debt lawsuits generated in the Alausí canton, province of Chimborazo (Ecuador). The results show that the subpoena by radio broadcasting does not violate the right to privacy or compromise the personal integrity of the parties to the proceedings because the purpose of this procedure is to inform the defendant about the content of the lawsuit so that he/she can propose exceptions or respond to itcorrelational conclusions and recommendations have been formulated. They aim to capture relevant information for the studied subject.